2013
DOI: 10.1097/mph.0b013e318279e509
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Knowledge and Perceptions Regarding Vitamin K Prophylaxis in Newborns

Abstract: There is a need to provide expecting parents with information regarding safety, utility, and benefits of VK prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 16 publications
0
24
0
3
Order By: Relevance
“…3 A one-time, prophylactic intramuscular (IM) injection of vitamin K at birth, recommended by the American Academy of Pediatrics (AAP) since 1961, had virtually eliminated this serious disease of newborns. 1 Recently, there have been increasing numbers of reports of parents refusing the vitamin K injection for their newborns in the United States 4–9 and an increase in the number of reports of infants with VKDB. 4,8 …”
mentioning
confidence: 99%
“…3 A one-time, prophylactic intramuscular (IM) injection of vitamin K at birth, recommended by the American Academy of Pediatrics (AAP) since 1961, had virtually eliminated this serious disease of newborns. 1 Recently, there have been increasing numbers of reports of parents refusing the vitamin K injection for their newborns in the United States 4–9 and an increase in the number of reports of infants with VKDB. 4,8 …”
mentioning
confidence: 99%
“…VKDB can be severe, and may present as spontaneous intracranial or gastrointestinal hemorrhage (Zipursky 1999; Sutor et al 1999; Winckel et al 2009). Although there currently is no active surveillance of VKDB or prophylaxis administration in the United States (U.S.), U.S. and foreign medical literature seems to have noted an increase in both parental refusal of vitamin K prophylaxis and VKDB in the past few years (Schulte et al 2014; Woods et al 2013; Eventov-Friedman et al 2013). …”
Section: Introductionmentioning
confidence: 99%
“…22 Looking beyond our scenario, clinicians who care for newborns may need to ally with obstetric clinicians to inform expectant parents about newborn preventive health measures. In a recent study, 69% of expectant parents did not know the purpose for vitamin K, 23 indicating a need for education and counseling before delivery. A different study showed increased likelihood of vitamin K refusal among those who chose midwife delivery, suggesting a role for targeted prenatal counseling by trusted providers who care for those most likely to decline it.…”
Section: Melissa Weddle MD Mph Commentsmentioning
confidence: 99%